2017
DOI: 10.2308/accr-51926
|View full text |Cite
|
Sign up to set email alerts
|

When Do Auditors Use Specialists' Work to Improve Problem Representations of and Judgments about Complex Estimates?

Abstract: Auditors are more likely to identify misstatements in complex estimates if they recognize problematic patterns among an estimate's underlying assumptions. Rich problem representations aid pattern recognition, but auditors likely have difficulty developing them given auditors' limited domain-specific expertise in this area. In two experiments, I predict and find that a relational cue in a specialist's work highlighting aggressive assumptions improves auditors' problem representations and subsequent judgments ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Other studies are taking into consideration the areas where such risks can arise and document potential concerns. For instance, Griffith (2018) considers that pattern recognition is important when dealing with highquality audit judgments. Moreover, he suggested that auditors' epistemic motivation to incorporate the cue into their problem representation occurs only in the presence of a situational factor as risk.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies are taking into consideration the areas where such risks can arise and document potential concerns. For instance, Griffith (2018) considers that pattern recognition is important when dealing with highquality audit judgments. Moreover, he suggested that auditors' epistemic motivation to incorporate the cue into their problem representation occurs only in the presence of a situational factor as risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton proposes that auditors use the client's perspective, that is, take into account the circumstances that the client was facing when preparing the financial statements, especially if there are indications of intentional misstatements [97].…”
Section: Auditorsmentioning
confidence: 99%
“…Prior research has shown auditors' judgments and decision-making processes are sensitive to audit risk. For example, high audit risk increases evidence recall (Sprinkle and Tubbs 1998), increases time spent reviewing working papers (Bamber et al 1988;Bamber and Bylinksi 1987), and affects client-acceptance decisions (Johnstone 2000) as well as the effective use of information from specialists (Griffith 2018). accuracy goals), they will select the most effective audit procedures, without limiting this choice to just the set of traditional procedures.…”
Section: Goal Activation Theorymentioning
confidence: 99%
“…In examining the effect of an AJR on auditors' pursuit of more innovative procedures, we also consider the moderating effect of audit risk as auditors' judgments and processes have been documented to be sensitive to audit risk (e.g., Griffith 2018;Johnstone 2000;Sprinkle and Tubbs 1998). When audit risk is relatively high, there is a greater need for audit procedures that will be effective in providing reasonable assurance that the financial statements are free from material misstatements (i.e., lower detection risk).…”
Section: Introductionmentioning
confidence: 99%